Pengaruh Stres Kerja terhadap Kinerja Karyawan dengan Variabel Intervening Kepuasan Kerja - Safrizal, Helmi Buyung Aulia (BISMA (Bisnis dan Manajemen), 2018)
Job stress is a dynamic condition in which an individual is confronted with an opportunity, constraint, or demand related to what he or she desires and for which the outcome is perceived to be both uncertain and important. The result of job stress is employees become nervous, feel chronic anxiety, increased strain on the emotions, thought processes and physical condition. Further, work stress can threaten and disrupt the employee in completing the work. The purposes of this research are: 1) to analize whether job stress factors that include environtmental, organizational and individual partially have significant direct influence to job satisfaction; 2) to analize whether job satisfaction have significant direct influence to job performance; 3) to find out whether job stres factor that include environtmental, organizational and individual partially have significant indirect influence to job performance. The result of this research are: 1) Job stress factors that include environtmental, organizational and individual partially have significant direct influence to job satisfaction; 2) job satisfaction have significant direct influence to job performance; 3) job stress factor that include environtmental, organizational and individual partially have significant indirect influence to job performance